ANALISIS PENERAPAN ARM’S LENGTH PRINCIPLE PADA TRANSAKSI PEMBAYARAN ROYALTI ATAS PEMANFAATAN MEREK DAGANG (TRADEMARK) KEPADA PERUSAHAAN AFILIASI - Hukamawati, Dinartika; Andriani, Arifah Fibri (JURNAL INFO ARTHA, 2016)
Trademark is a unique marketing intangible. It does not only involve the expenses of marketing, advertising,  and  promoting,  but  the  reputation  of  the  trademark's  owners  also  takes  part  in  the development of trademark. Many parties involve in the development of trademark. In the context of transfer pricing, these parties entitle to some compensation. And arm's length principle must be applied to determine the reasonable compensation for the use of trademark. Transaction payment of royalties on trademarks is subject to taxes.The  taxation  of  transactions  payment  of  royalties  on  the  use  of  the  trademark  among  affiliated companies also created  disputes between the taxpayer and Tax collector. Cases disputed are related to the fairness of the transaction relating to the determination of royalty payments on trademarks which cover:  definition,  identification,  allocation  and  valuation  between  affiliated  companies  (Caroline Silberztein, 2010). The dispute raises the burden of the cost of compliance for taxpayers and cost of collection to the tax authorities.This study aims to determine how to identify ownership and economic benefits, as well as the best method which can be applied to determine the reasonable price of royalty payment transaction for the trademark use.The results shows that in order to determine the parties entitled to compensation/ remuneration are: Party who can be legally declared to have legal ownership (legal owner) which are parties that have control over decisions related to the exploitation of the intangible as well as the right to restrict others to use intangible; Parties that contribute to the value of the trademark by identifying the parties who bear the cost and risk of the development of the trademark.